PENGEMBANGAN MEDIA POWERPOINT IPA INTERAKTIF MATERI ENERGI UNTUK SISWA KELAS 3 SDN 2 GONDANG - Rahmawati; Erfan, Muhammad; Wira Zain Amrullah, Lalu; Handika, Ilham (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the validity and practicality of interactive PowerPoint media. This research is R&D (Research and Development) research. The research model used is ADDIE with five stages, namely analysis, design, development, implementation and evaluation. The data collection instruments used include observation, interviews, questionnaires, and documentation. Data collection uses validity and practicality analysis. The validation results from material of experts received a value of 87%. The validation results from media experts received a value of 90% with a validity category. In the results of the student response, students got a value of 93.58%, while the results of the teacher's response got a score of 100% in the practicality.